LDLR rs2228671 gene polymorphism and relationship with the development of familial hypercholesterolemia and obesity in military police officers officers - Ferreira, Fábio Castro (2023)
The polymorphism of the LDLR gene (LDL cholesterol receptor) is associated with lipid alterations, such as familial hypercholesterolemia (FH), caused by mutations in the genes that produce LDLR catabolic and uptake proteins. The objective of this study was to associate the polymorphism of the LDLR gene rs2228671 (C/T) with dyslipidemia in military police officers in the State of Goiás. The case-control study evaluated samples from 200 military police officers, by lipid profile measurement and by qPCR (real-time polymerase chain reaction) to identify possible associations between dyslipidemias, FH and LDLR gene polymorphism. Of the military police officers, 93% were male. In the lipid profile, 58% belonged to the group with the presence of a degree/class of dyslipidemia. The genetic analysis of the case group, the LDLR gene showed 68.1% of the CC genotype, 19.8% TC and 12.1% TT. In the control group, the genotype was CC in 82.1%, CT in 14.3% and TT in 3.6%. Lipid and BMI parameters were analyzed between the case and control groups. The dominant heterozygous genotype CT, 4.4% of the police officers exhibited TC ≥310 mg/dL with a positive diagnosis of FH and 95.6% CT <310 mg/dL, representing a probable diagnosis of FH. In the TT genotype, 100.0% of the police officers had TC <310 mg/dL, with a negative diagnosis for FH. The C allele of the LDLR rs2228671 gene in CC-dominant homozygosity and CT-dominant heterozygosity presents a high risk for the development of FH and obesity compared to the T allele.